Aprendizagem de conceitos de eletrodinâmica para o ensino médio: construção e implementação de uma UEPS - SILVA, Frank Herik Valente (2021)
The lack of interest in the study of the physical discipline has several causes, among them, deficit teaching is highlighted. This, considered traditional and strongly dependent on the textbook, is usually practiced through classes based on the transmission and accumulation of content, in which students passively receive the information and make resolutions and demonstrations based on formulas, which are determined by the teacher. In order to improve this scenario, we propose to analyze the teaching of certain concepts of electrodynamics, such as electric current, resistors, association of resistors in series and in parallel, electric power and electric energy, through the use of the theory of meaningful learning from the development and application of experiments constructed with alternative materials of easy acquisition to promote the integration of theoretical and practical activities through two didactic sequences. These sequences supported the development of an experimental kit composed of association of lamps connected in parallel and in series triggered by simple switches and in parallel with scripts and basic texts on the theoretical foundations of concepts presented in the classroom. The study was carried out with the collaboration of students of the 3rd year of high school of a public school of the state school located in the city of São Luís - Maranhão. The theoretical contribution of this work was based on the assumptions of Significant Learning by David Ausubel, on the guidelines for the elaboration of Potentially Meaningful Teaching Units (PMTU) by Marco Antônio Moreira and on research results on types of experimentation. The teacher's logbook, writings produced by the students, discussions, content evaluations, exhibition of experiments and questionnaires were used as data collection instruments. Considering aspects such as the effective participation of students throughout all the stages planned for the development of the proposed PMTU and the analysis of the data obtained through a qualitative approach, we can conclude that the educational product developed can contribute to the teaching and learning process, because its results obtained clearly demonstrate signs of meaningful learning on the part of students bringing subsidies both to teachers and students in relation to the improvement of physics teaching.